Improving Students’ Reading Comprehension Through Powtoon Application - Ririn Hariyanti; Emeliya Sukma Dara Damanik (South Sulawesi Education Development (SSED), 2024)
Reading comprehension is a fundamental skill that plays a crucial role in student's academic success across various disciplines. Powtoon is a user-friendly digital tool that allows users to create engaging animated presentations and videos. With its intuitive interface and customizable features, Powtoon offers educators a creative platform to design interactive learning materials that can captivate students' attention and facilitate comprehension of complex textual content. This research aims to investigate the effectiveness of utilizing the Powtoon application in improving students' reading comprehension skills. Researchers uses quantitative method. The population in this study is all students of Ad-Durrah Junior High School in Medan. Sampling will be done randomly (cluster random sampling), where each class has an equal opportunity to be a research sample. Two classes will be sampled, consisting of one control class and one experimental class. The result shows that the use of powtoon as a medium to improve students' reading comprehension. This media is a creative and innovative way to make a learning video in teaching English, which can stimulate students to learn and not be bored in reading a text.